(3TQM eNJUQ GdbOhQj aj Gdabgs - (3eLghds ((3jhfS Hf jYbhH Hf eMeOs)
(3ChdgG (B:s
(3hChd eG ajg HOfg hef JhVC hde jSe Gddg JYGdi cGf WghQG deG CUGHg GdeGA hGMJL HYVge aj EjLGH GdJSejI dG hVhA def de jSe Gddgs
(3BNQgG (B:s
(3hddRhL ef GdeSCdI GdKGfjI SHYI CSge hbOQg ef GdOQge MHI hKdGKI CQHGY MHI hddHfJ eSCdI hddGHf VYag KdGK MHGJ hfUa MHIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3Gdabg GdMfHdjs